Attachment Styles and Attachment Based Change in Offenders in a Prison Therapeutic Community. Issue 3 (27th May 2019) - Miller, S.; Klockner, K.
ABSTRACT: A democratic prison Therapeutic Community (TC) aims to facilitate personal growth through enhanced interpersonal relationships. This study used a four category model of adult attachment to assess TC offenders' relationships, obtained from a novel self-report method (a card sorting task). Four styles of attachment were empirically evidenced and an examination of individual attachment styles pre- and post-twelve months of treatment revealed a decrease in insecure attachments and an increase in secure attachment. Burglary/theft/robbery offenders were mainly fearful-avoidant at time one and preoccupied or secure by time two; sexual offenders were mostly preoccupied at time one and hybrid attached by time two; and violent offenders had lower fearful and preoccupied attachments and higher secure attachment rates by time two, but also more dismissive attachments. The findings are encouraging given the role of insecure attachment in the maintenance of offending behaviour and confirm that attachment theory can be usefully applied within this setting.